The Role of Yoon Yeon Woo in Supporting the Story of the Drama My Perfect Stranger Directed by Kang Soo Yeon - Eny Suprihandani; Nurul Auliya Ariska; Ikhwan Muslim (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
The study was written to fulfil the writer’s final examination with the subject is The Role of Yoon Yeon Woo in Supporting The Story of The Drama My Perfect Stranger Directed By Kang Soo Yeon. The objectives of this study are: first, to identify Yoon Yeon Woo’s character in the drama My Perfect Stranger. Second, to find out Yoon Yeon Woo’s conflict in the drama My Perfect Stranger, and the third is to identify Yoon Yeon Woo’s role in supporting the story in the drama My Perfect Stranger. In this study, the writer of this study uses the qualitative research,because it focuses on understanding social phenomena from the perspective of the human participants in natural setting.The discussion focused on internal or a character in the drama. My Perfect Stranger is a mystery fantasy drama that tells about 2 main character in the drama went to time travel to year 1987 for uncover the serial murderer happen in Woojung-ri village and fix their future life. Hopefully this research will be useful, and in the future this research can become a source of data for future researchers who will conduct research on the same or related themes.